THE GENE POOL FOR BREEDING OF CARROT AND TABLE BEET - V. I. Burenin; T. M. Piskunova; T. V. Khmelinskaya (Овощи России, 2017)
The collection of carrot and table beet in Russia has more than 400 varieties and hybrids, included in the State Register of the Russian Federation. In domestic assortment of carrot, the proportion of F1 hybrids is about 50%, beet – about 20%. The most domestic varieties of root crops are characterized by a high level of adaptability with combination of high yield, resistance to biotic and abiotic stresses. Varieties and hybrids of carrot and beet originated from domestic breeding programs exceed on an average estimation the foreign ones in contents of dry matter, sugars, betanin and carotenoids. They better retain high root qualities during long-term storage. In the breeding of varieties of carrots and table beets, it is important to take into account the suitability to machine harvesting. Varieties with erect leaf rosette and solid leaf attaching to the root head are better adapted to mechanized harvesting. The use of industrial technologies in the production of beet root in large amounts depends on the availability of monogerm varieties that gave mechanized formation of plantations. An important role in solving these problems belongs to the use of the breeding of a diverse initial material. The 250 carrots accessions and 165 table beet accessions were studied in the Pushkin laboratories of VIR (Pushkin, Leningrad region). Evaluation of collection accessions on the complex of valuable traits was carried out. As a result of study, initial breeding material for high yield, early-maturation, high quality of production, bolting, resistance to diseases and pests, suitability for mechanized cultivation has been selected and recommended.